ATTITUDES OF THE LOCAL POPULATION ON THE DEVELOPMENT OF CYCLING TOURISM - A CASE STUDY OF THE WEST BACKA DISTRICT - Lakić, Nemanja; Pivac, Tatjana; Besermenji, Snežana; Bajkanović, Jovana; Jurišin, Ivica (The Business of Tourism, 2024)
Cyclotourism, i.e. bicycle tourism, has experienced an extraordinary rise in recent years, in Europe, as well as in our country.In accordance with the wishes, needs and habits of the modern tourist who wants a new type of educational, adventurous and physically active holiday, and which finds its foothold in the development of this form of selective tourism.The modern tourist spends his free time (vacation) actively, that is, he tries to adapt to the life of the local population, where he learns the authenticity of the tourist destination.The task of the research is to examine the cycle tourism resources of West Backa district as well as to point out potential shortcomings in order to further develop this type of tourism as a special form of tourist offer.For the purposes of the work, a questionnaire was used, on the basis of which the conclusion was reached that the ongoing project "Amazon of Europe Bike Trail" has insufficiently improved the existing cycle tourism resources as well as the cycle infrastructure of this region.